Potential of Antioxidant Activity Caulerpa racemosa Extract Using DES Solvent and Different Sonication Times as An Antibacterial Against Pathogenic Bacteria - Satyantini, Woro Hastuti; Mukti, Akhmad Taufiq; Bakhri, Saiful (Journal of Aquaculture and Fish Health, 2024)
Caulerpa racemosa, a type of green algae, has been studied  for its potential health benefits, including antioxidant and an- tibacterial properties. The extraction of bioactive compounds  from marine algae using green solvents like Deep Eutectic Sol- vents (DES) has gained interest due to their efficiency and en- vironmental friendliness. This research aimed to determine  the potential antioxidant activity of C. racemosa extract using DES solvents and different sonication times as an antibacterial  against pathogenic bacteria. The research employed a Facto- rial Completely Randomized Design (CRD) with two variables:  sonication time (10, 20, and 30 minutes) and different DES solvents (ethanol and ethylene glycol (1:20) with 90% aquades, and methanol and glycerol (1:10) with 90% aquades. The highest antioxidant activity was found in DES  Methanol-Glycerol (36.39 mg TE/g dw), followed by DES Eth- anol-Ethylene glycol (28.30 mg TE/g dw), both significantly  different (p<0.05). The C. racemosa extract inhibited the growth of V. parahaemolyticus with an inhibition zone of 8.08 mm at 50 ppm and 13.13 mm at 1,000 ppm. For V. harveyi, inhibition started at 6.37 mm at 50 ppm, reaching 11.70 mm  at 1,000 ppm. DES Methanol-Glycerol with a 10-minute soni- cation provided the highest antioxidant activity and effectively  inhibited V. parahaemolyticus and V. harveyi. Extraction of C. racemosa with DES-MG solvent and varying sonication times influences its antioxidant activity and antibacterial properties.